Adolescents' Perceptions of Childbirth. Issue 4 (July 2020) - Anderson, Cheryl Ann; Baker, Kathy; Harter, Lindsay
Abstract: Purpose: The purpose of this study was to describe adolescents' perception of birth within the first 72 hours postpartum. Study Design & Methods: A thematic analysis using qualitative data captured via one overarching question about labor expectations as part of a larger, parent quantitative study exploring psychological birth trauma. Results: Forty-two percent ( n = 128) of adolescents ages 13 to 19 in the original study responded in writing to one overarching question concerning birth expectations. Four major themes were identified including pain, support, personal control, and fear, with three subthemes. Pain was expressed as a primary theme for all age adolescents and had an impact on all other themes. Expressed fear was general and specific including a fear of dying that emerged as a subtheme along with labor information and emotions. Clinical Implications: Lacking a positive birth experience has been linked with poor mental health outcomes (depression and posttraumatic stress) postpartum. Findings offer a guide for nurses and other healthcare providers to promote a positive birth experience for adolescents. Pain management is foremost to adolescents and requires healthcare providers' continued attention. Working together with adolescents to identify and monitor level of pain; assess support needs, feelings of loss of personal control, and signs or verbal expressions of fear; and offer ongoing information about labor progress and necessary procedures can help strengthen bonds between teens and their healthcare provider and create a positive birth experience. Abstract : This qualitative study of adolescents' experiences during labor and birth provides rich data about the vulnerable population of teen mothers. Findings offer suggestions for nursing care that can support teen mothers giving birth based on their concerns, expectations, and preferences.